Assessment of the validity of the quenching method for evaluating the role of reactive species in pollutant abatement during the persulfate-based process - Gao, Lingwei; Guo, Yang; Zhan, Juhong; Yu, Gang; Wang, Yujue (Water research (Oxford), 2022)
•Effects of six commonly used quenchers on the Co(II)/PMS process mechanism were evaluated.•Adding high-concentration quenchers considerably changed the Co(II)/PMS process mechanism.•The underlying assumption of the quenching method is unrealistic.•The quenching method may misinterpret the role of SO4•−, •OH, and 1O2 in pollutant abatement.•The confounding effects of quenchers were clarified using probe-based kinetic modelling. Reactive species such as sulfate radicals (SO4•−), hydroxyl radicals (•OH), and/or singlet oxygen (1O2) have often been proposed as the main reactive species for pollutant abatement during the persulfate-based process, and their relative importance is conventionally assessed by the quenching method based on an implicit fundamental assumption that the added high-concentration quenchers (e.g., tert-butanol and methanol) only scavenge their target reactive species, but do not considerably affect the other reaction mechanism of the system. To examine the validity of this assumption, this study evaluated the effects of several commonly used quenchers (tert-butanol, methanol, ethanol, isopropanol, furfuryl alcohol, and L-histidine) on the mechanism of a cobalt mediated peroxymonosulfate (Co(II)/PMS) process. The results demonstrate that besides quenching target reactive species, the added high-concentration quenchers can cause many confounding effects on the Co(II)/PMS process, e.g., accelerating PMS decomposition, interfering reactive species production, and quenching of non-target reactive species. Because of these confounding effects, the quenching method can actually lead to serious misinterpretation of the role of reactive species in pollutant abatement during the persulfate-based process. The findings of this study highlight that the underlying assumption of the quenching method is usually invalid for the persulfate-based process. Therefore, it should be cautious to apply the quenching method to investigate the mechanism of the persulfate-based process, and some debatable conclusions of prior studies obtained with the quenching method may require further verification. [Display omitted]